Intermolecular Visible‐Light Photoredox Atom‐Transfer Radical [3+2]‐Cyclization of 2‐(Iodomethyl)cyclopropane‐1, 1‐dicarboxylate with Alkenes and Alkynes. Issue 36 (31st July 2013) - Gu, Xiangyong; Li, Xiang; Qu, Yue; Yang, Qi; Li, Pixu; Yao, Yingming
<x xml:space="preserve">Abstract</x> Radical chemistry! A visible‐light‐promoted, tin/boron‐free intermolecular [3+2] atom‐transfer radical cyclization reaction was developed by using iridium polyphenylpridinyl complex as the sensitizer (see scheme). 2‐(Iodomethyl)cyclopropane‐1, 1‐dicarboxylate reacted with various alkenes and alkynes to form cyclopentane and cyclopentene derivatives.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>